2021
DOI: 10.29244/jpsl.11.1.93-100
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between air pollutants and COVID-19 cases and its implications for air quality in Jakarta, Indonesia

Abstract: World Health Organization (WHO) has announced that COVID-19 as a global pandemic and public health emergency. Previous studies have revealed that COVID-19 was an infectious disease and it could remain viable in ambient air for hours. Therefore, this study aims to examine the correlation between air pollutants (PM2.5, PM10, CO, SO2, NO2 and O3) and COVID-19 spread in Jakarta, Indonesia. Furthermore, this study also evaluates the impact of large-scale social restriction (LSSR) on air pollution index (API). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
7
0
3
Order By: Relevance
“…Another study found that exposure to SO 2 , CO, and PM 2.5 made an area more susceptible to Covid19 infection. Nonetheless, this result is also closely related to climatic factors such as temperature, precipitation, and wind speed (11).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another study found that exposure to SO 2 , CO, and PM 2.5 made an area more susceptible to Covid19 infection. Nonetheless, this result is also closely related to climatic factors such as temperature, precipitation, and wind speed (11).…”
Section: Discussionmentioning
confidence: 85%
“…The quality standard of air pollutants in Indonesia In March 2020, large-scale social restrictions were implemented in Jakarta to reduce the spread of Covid19. The impact was also seen in the changes in Jakarta's air quality, which appeared to decrease by 15.74% for PM 10 , 6.26% for SO 2 , 29.17% for CO, and 18.34% for NO 2 , as well as an increase of 4.06% for O 3 (11).…”
Section: Hazard Identificationmentioning
confidence: 92%
“…Furthermore, encouraging polycentric urban form can be an alternative future metropolitan development to reduce commuting behavior (Hudalah and Firman, 2012). It is worth noting that, stimulated by the current pandemic situation, the change of work behavior from work from office to work from home has been proven to function well and to reduce emissions (Rendana and Komariah, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5 It is estimated that there were more than 5.5 million air pollution-related disease cases in Jakarta in 2010, including 2.45 million cases of ARI. 9 A previous study has discussed that ambient air pollutants have an essential role in contributing to the high respiratory infection ratio by making people more vulnerable to the virus. 10 The WHO also reported that seven million die annually because of fine particles in the polluted air.…”
Section: Introductionmentioning
confidence: 99%